Optimalisasi untuk Menghasilkan Efisiensi Ideal Turbin Uap Pembangkit Listrik TenagaBiomassa Kapasitas 20 MW - Habibi Santoso (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2018)
The energy crisis is one of the problems facing by Indonesia. One solution to overcome this problem is turning waste into electricity, leading to a solution to the long-standing waste problems in many areas in Indonesia. This research is part of the initial design of PLTU with Biomassa (Waste) energy sources. This research covers the initial design of the rankine cycle that includes determining the type of turbine to be used, whether the reaction turbine or impulse turbine and the number of turbine shaft and determining a simple, regenerative cycle or another modified cycle. The step taken is comparing thermodinamically the advantages and disadvantages of the simple rankine cycle with the regenerative cycle. The parameters used as the standard of comparison are thermal efficiency, net work and work ratio. From the calculation results, it is determined to use a steam turbine with the type of one-shaft impulse turbine using a regenerative cycle with 3 feedwater heaters because it can increase efficiency up to 50% when compared to a simple regenerative cycle with efficiency of 37%.